Education in Ireland: accessible without discrimination for all?. Issue 10 (25th November 2020) - Doyle, David M.; Muldoon, Marie; Murphy, Clíodhna
ABSTRACT: While Article 13 of the International Covenant on Economic, Social and Cultural Rights articulates a comprehensive right to education, truly accessible education remains elusive in many countries. This article considers the accessibility of education in Ireland in law, policy and practice, drawing on semi-structured interviews with politicians, educators, and representatives of various relevant interest groups. The Irish education system, once described as a 'Church-State co-operative', has historically been controlled by the Catholic Church, but in recent times has been obliged to adapt in order to cater for an increasingly ethnically and culturally diverse school population. The article concludes that a variety of exclusionary practices have facilitated the establishment of a de facto two-tiered education system in Ireland, with marginalised groups such as asylum-seekers; religious minorities; and the indigenous Traveller community particularly disadvantaged. A recent process of legislative reform addresses some key issues, such as admission policies, which distinguish prospective students on the basis of religion, past pupil parents, and when their name was placed on the enrolment list. However, it remains to be seen whether these reforms will significantly enhance access in practice.